(untitled) (Nativa, 2020)
Objetivou-se com esta pesquisa analisar as principais posturas adotadas na atividade de corte semimecanizado da Mimosa tenuiflora (Willd.) Poir. popularmente conhecida como jurema preta, por meio da utilização dos métodos ergonômicos Ovako Working Posture Analysis System (OWAS), Rapid Upper Limb Assessment (RULA) e Rapid Entire Boby Assessment (REBA) além de propor melhorias no ambiente de trabalho. Foram analisadas, em cada um dos métodos, 220 posturas adotadas durante a atividade de derrubada, destopamento, toragem e condensadas em 30 codificações principais. Dado o exposto, concluiu-se que as codificações em que o operador se manteve com as costas inclinadas, inclinadas e torcida, os dois braços acima dos ombros, o antebraço com amplitudes maiores que 45°, com o pescoço inclinado, e o troco inclinado, além de todas as posturas que foram classificadas nas categorias ou níveis de ação que indiquem uma intervenção próxima ou imediata. Palavras-chave: ergonomia; biomecânica; exploração florestal. ANALYSIS OF THE POSTURES ADOPTED DURING THE SEMIMECANIZED COURT OF JUREMA PRETA IN CAATINGA MANAGEMENT ABSTRACT: The objective of this work was to analyze the main postures adopted in the semimechanized cutting activity of Mimosa tenuiflora (Willd.) Poir., popularly known as black jurema, through the use of Ovako Working Posture Analysis System (OWAS), Rapid Upper Limb Assessment (RULA) and Rapid Entire Boby Assessment (REBA) in addition to proposing improvements in the work environment. In each method, 220 postures adopted during the felling, delimbing and tracing activity were analyzed and condensed into 30 main codings according to the result obtained for each of the analysis methods and further subdivided according to the activity. felling, delimbing and tracing. Given the above, it was concluded that the codings in which the operator stands with the back inclined, bent and twisted, both arms above the shoulders, the forearm with amplitudes greater than 45 °, the forearm with amplitudes greater than 45 °, the neck is at some angle of inclination, the inclined change, and all postures that have been classified into categories or levels of action that indicate close or immediate intervention. Keywords: ergonomics; biomechanics; caatinga management.